Modulation of oxidative stress by Centella asiatica (l.) urb. Leaves against carbon tetrachloride-induced hepatic damage in rats - Mohammad Iqbal; Mohammad Amil Zulhilmi Benjamin; Ping-Chin Lee (Universiti Malaysia Sabah, 2025)
Liver injury induced by oxidative stress remains a significant global health concern, necessitating the exploration of safe and effective hepatoprotective agents derived from natural sources. Centella asiatica (L.) Urb., frequently referred to as ‘pegaga’, is a plant renowned for its notable medicinal attributes. The primary aim of this study is to assess the antioxidant capacity and hepatoprotective activity of the ethanolic extract of C. asiatica (EECA). The assessments used to evaluate EECA for its antioxidant properties included total phenolic content (TPC), as well as 2,2-diphenyl-1-picrylhydrazyl (DPPH) and reducing power assays. Additionally, the study evaluated the ability of EECA to mitigate experimentally induced hepatic injury in Sprague-Dawley rats caused by carbon tetrachloride (CCl₄) at 100, 500, and 1,000 mg/kg b.wt. doses. Biochemical assays included measuring hepatic marker enzymes alanine transaminase (ALT) and aspartate transaminase (AST) in serum, as well as evaluating malondialdehyde (MDA) and reduced glutathione (GSH) levels in liver homogenates. The TPC of EECA was 106.55 ± 2.23 mg GAE/g. Its DPPH and reducing power assays exhibited moderately potent antioxidant attributes compared to standard references. Nonetheless, groups subjected to CCl₄ displayed notably elevated levels of ALT and AST, increased MDA, and decreased GSH. Pretreatment with EECA resulted in a marginal decrease in hepatic marker enzyme activity, with reductions in ALT (14% to 2-fold), AST (25% to 3-fold), and MDA (15– 57%), along with an increase in GSH (3–23%). These findings imply that EECA contains active constituents capable of mitigating the hepatotoxic effects induced by CCl₄.